Surface characterization of magnesium fluoride thin films prepared by a fluorine trapping based non-reactive sputtering technique. (December 2016) - De, Rajnarayan; Haque, S. Maidul; Tripathi, S.; Rao, K. Divakar; Prathap, C.; Kumar, Mohit; Som, T.; Sahoo, N.K.
Abstract: Successful deposition of magnesium fluoride thin films by a non-conventional magnetron sputtering technique is reported here followed by the analysis of their optical, morphological and structural properties. The drawback in the external supply of health hazardous fluorinated gases in the context of fabricating fluoride films by conventional sputtering processes was completely eliminated by trapping the dissociated fluorine gas inside the chamber during deposition. The dependencies of basic thin film properties stated above on magnetron energizing power were investigated. Qualities of surface structures were analyzed on the basis of surface roughness and surface correlation function parameters. A qualitative correlation of film morphology with optical properties of such fluoride films was observed in the present study. Film growth rates were found to have great importance in deciding the surface topography of the films. Careful investigation of film structure clearly revealed a remarkable increase in crystallite size with the increase in sputtering power. The composition of the film is maintained throughout the studied power range as seen by X-ray photoelectron spectroscopy. Finally, optimum sputtering power for film deposition was decided by taking into consideration the quality in surface structure together with optical quality of the films. Highlights: MgF2 films were made by non-conventional RF sputtering based on fluorine trapping. A strong correlation is seen between the surface and optical quality of the films. Film growth rate influences the surface topography of the films. Sputtering power is optimized on the basis of optical and surface quality.